2022
DOI: 10.1002/curj.147
|View full text |Cite
|
Sign up to set email alerts
|

How early mathematics interventions support mathematics vocabulary learning: A content analysis

Abstract: While there is a strong research base that supports intervening early in mathematics, research investigating the importance of mathematics vocabulary is still emerging. Practitioners and researchers may benefit from understanding how mathematics interventions support mathematics vocabulary acquisition, particularly for students who struggle with learning mathematics. Thus, the purpose of this study was to conduct a mathematics vocabulary content analysis across seven kindergarten and first‐grade mathematics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This has implications for both parents and educators. For example, one study found that math interventions for early learners are often absent of explicit recommendations related to literacy integration, such as disciplinary vocabulary (Nelson & Carter, 2022). Thus, curriculum developers should more closely evaluate how to plan instruction that leverages literacy to promote math.…”
Section: Discussionmentioning
confidence: 99%
“…This has implications for both parents and educators. For example, one study found that math interventions for early learners are often absent of explicit recommendations related to literacy integration, such as disciplinary vocabulary (Nelson & Carter, 2022). Thus, curriculum developers should more closely evaluate how to plan instruction that leverages literacy to promote math.…”
Section: Discussionmentioning
confidence: 99%
“…Each lesson also included at least one of the following instructional strategies: (a) repetition of the word and word meaning; (b) opportunities to communicate verbally with other students using the word (e.g., using the word in a sentence); (c) identification of similar and opposite terms; (d) practice spelling the new word; and (e) applying the word meaning using equations, pictures, and physical manipulatives. To identify these instructional strategies, we referenced guidelines for teaching academic vocabulary (Monroe & Panchyshyn, 1995; Pierce & Fontaine, 2009; Riccomini et al, 2015), along with the results of a previous study that examined trends and gaps in how kindergarten and first–grade early numeracy intervention programs incorporated mathematics vocabulary (Nelson & Carter, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This struggle is problematic, given that understanding and applying mathematics vocabulary is necessary not only in solving word problems but also in communicating mathematical thinking in real–world settings (Pierce & Fontaine, 2009). While many researchers have emphasized the importance of mathematics vocabulary, it is not always explicitly taught within intervention lessons for students who receive supplemental support (Nelson & Carter, 2020). The efficacy of mathematics vocabulary interventions has not reached consensus, perhaps due to the relative lack of research in this area.…”
mentioning
confidence: 99%
“…In this respect, the early years context is particularly significant. Research suggests that many socially disadvantaged children in early years are less likely to develop their spoken language and vocabulary [11], which makes early interventions essential to address issues around language skills and mathematics knowledge [12,13]. Nevertheless, there appears to be a research and practice gap in terms of how to prepare teachers to address language diversity in classrooms [14][15][16][17] to develop meaningful interventions.…”
Section: Introductionmentioning
confidence: 99%